The Influence of CAR and SIZE on Intermediation through Digital Transformation Efficiency in State-Owned Banks and Regional Development Banks for the 2010-2024 Period - Alvira Nur Fitri; Faishal Fadli (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the effect of Capital Adequacy Ratio (CAR), bank size (SIZE), and digital transformation efficiency on banking intermediation, as well as the role of digital efficiency as a mediator in state-owned banks and regional development banks in Indone-sia. Annual financial report data from 2010 to 2024 were analyzed using panel data re-gression (CEM) and Sobel's test. Intermediation is measured by LDR, while digital efficien-cy is measured by the ratio of IT costs to total operating costs. The results show that in regional banks, CAR and SIZE have a significant positive effect on intermediation, and digital efficiency mediates this relationship (z = 2.07; p = 0.038; z = 2.42; p = 0.015). Meanwhile, in state-owned banks, digital efficiency only has a direct effect on intermedia-tion without a mediating effect, and NPL is not a distinguishing factor in the intermediation mechanism. These findings emphasize the importance of efficient digital capabilities to drive intermediation, especially in regional development banks.